(untitled) (Research, Society and Development, 2026)
Objective: To describe the patterns and assess the prevalence of poor sleep quality and associated factors in students from a university in southern Santa Catarina. Methods: Cross-sectional study with a convenience sample of students from the Federal University of Santa Catarina, Araranguá campus. Data were collected using a semi-structured questionnaire via Google Forms. The outcome of the study was sleep quality assessed using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Results: The study included data from 272 students. The prevalence of poor sleep quality was 50%, with lower socioeconomic status (D/E), being a former smoker, and having greater severity of depressive symptoms being associated with higher prevalences of the outcome. Conclusion: The data suggest that different socioeconomic levels influence sleep. Furthermore, smoking and symptoms of depression are factors of concern when assessing sleep quality in this population. Identifying risk factors allows for the development of targeted interventions for the most affected groups.